Primer registro de Cyathea fulva (Cyatheaceae, Polypodiopsida) en el Estado de Mexico - Zepeda, C.=700 1 Monroy Vilchis, O.
(Es, En)
ilus., 20 ref
Keywords: CYATHEACEAE; TAXONOMIA; BIODIVERSIDAD; ANATOMIA DE LA PLANTA; MEXICO; BOLETIN DE LA SOCIEDAD BOTANICA DE MEXICO